Synergistic Effects of MXene and Cerium Hexaboride on Dielectric Relaxation, Impedance, and Thermal Stability of Polyvinyl Alcohol-Sodium Alginate Nanofibers - Erol, Ibrahim; Ismail, Ibrahim; Demirelli, Kadir; Aksu, Mecit; Tilyabov, Makhsudjon (Springer, 2026)
In this study, multifunctional PVA-SA-based nanofibers incorporating cerium hexaboride (CeB6) nanoparticles and MXene (Ti(3)CNTx) were successfully fabricated via electrospinning to develop advanced dielectric and thermally stable materials. Structural and morphological analyses confirmed the homogeneous integration of both fillers within the polymer matrix while preserving fiber integrity. The synergistic interaction between CeB6 and MXene played a critical role in enhancing interfacial polarization, charge transport, and thermal resistance. MXene incorporation increased the maximum degradation temperature from 311 degrees C to 327 degrees C, while significantly improving dielectric performance, with epsilon ' values reaching similar to 15-16 at higher loadings. In addition, capacitance values nearly doubled, indicating enhanced energy storage capability. Mechanistically, MXene sheets facilitated the formation of conductive pathways and strong interfacial dipolar interactions, whereas CeB6 served as a stabilizing phase and a charge-trapping center. This hybrid interaction resulted in reduced impedance and improved frequency-dependent electrical behavior. Overall, the developed CeB6-MXene/PVA-SA nanofibers exhibit tunable surface characteristics and enhanced multifunctional performance, making them promising candidates for flexible electronics, dielectric layers, sensor platforms, and energy-related applications.
Keywords: Pva; Sodium Alginate; Thermal Properties; Dielectric Properties; Electrosupun